Vogel's textbook of quantitative chemical analysis - Jeffery, G. H. (harlow: ELBS, 1989)
This book has been carefully restructured to present the basic theory alongside coverage of more practical subjects. This edition incorporates a much wider range of organic analyses, especially those which have a relationship to environmental topics, such as heavy metals, dissolved oxygen and chemical oxygen demand.
Includes bibliographical references; Appendix 819-854p.; Index 855-877p.
Keywords: Analysis; Chemistry; Quantitative; Quantitative; Chemistry